Yakuza fiancé = Raise wa Tanin ga Ii. 1 - Konishi, Asuka (Seven Seas Entertainment, 2022)
"Yoshino grew up the sheltered yakuza princess of the largest crime family in Osaka, the Somei. Due to her resting bitch face and dangerous family, no man has ever approached her. When her grandfather signs a truce with the Tokyo-based Miyama crime family, he offers her up as a truce bride to the Miyama leader's grandson! Kirishima Miyama is popular, charming, and seems totally normal. But behind his smile is a violent sadomasochist who thirsts for her dominance even more when she impresses him with her moxie! Even though she knows how bad yakuza can be, she's stunned by Miyama's viciousness. She can't turn him down with the East-West peace treaty on the line...so instead she steels herself to play ball!"--Publisher.